If we are given that $\alpha + \beta = 3$ and ${\alpha ^3} + {\beta ^3} = 7$, then show that $\alpha $ and $\beta $ are the roots of $9{x^2} - 27x + 20 = 0$.
Answer
Verified
473.1k+ views
Hint: To attempt this question the knowledge of the concept of quadratic equation is must and also remember to use algebraic formula like ${a^3} + {b^3} = \left( {a + b} \right)\left( {{a^2} + {b^2} - ab} \right)$ and ${a^2} + {b^2} + 2ab = {\left( {a + b} \right)^2}$ to simplify the equation, using this information you can approach the solution.
Complete step-by-step solution:
Now it is been given that $\alpha + \beta = 3$ and ${\alpha ^3} + {\beta ^3} = 7$. We need to show that $\alpha $ and $\beta $ are the roots of $9{x^2} - 27x + 20 = 0$
Now ${\alpha ^3} + {\beta ^3} = 7$ so using ${a^3} + {b^3} = \left( {a + b} \right)\left( {{a^2} + {b^2} - ab} \right)$
We can say that ${\alpha ^3} + {\beta ^3} = \left( {\alpha + \beta } \right)\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right)$
Putting values from above we get
$7 = 3\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right)$
$\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right) = \dfrac{7}{3}$
Now $\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right)$
Since we know that ${a^2} + {b^2} + 2ab = {\left( {a + b} \right)^2}$
So, we can rewrite the above equation as ${\left( {\alpha + \beta } \right)^2} - 3\alpha \beta $
${\left( {\alpha + \beta } \right)^2} - 3\alpha \beta = \dfrac{7}{3}$
Again, substituting the values, we get
$9 - \dfrac{7}{3} = 3\alpha \beta $
Hence $\alpha \beta = \dfrac{{20}}{9}$
Now if sum of roots and product of roots is given that the quadratic equation can be written as ${x^2} - (sum{\text{ of roots)x + product = 0}}$
Thus, the quadratic equation having roots $\alpha $ and $\beta $ is ${x^2} - (\alpha + \beta )x + \alpha \beta = 0$
So, putting values we get
${x^2} - 3x + \dfrac{{20}}{9} = 0$
Therefore, on solving we get
$9{x^2} - 27x + 20 = 0$ which is the desired equation.
Note: Whenever we face such problems the key concept that needs to be in our mind is if somehow, we get the sum and the product of the roots then we can easily get the required quadratic equation. Hence simply accordingly to obtain sum and product of roots.
Complete step-by-step solution:
Now it is been given that $\alpha + \beta = 3$ and ${\alpha ^3} + {\beta ^3} = 7$. We need to show that $\alpha $ and $\beta $ are the roots of $9{x^2} - 27x + 20 = 0$
Now ${\alpha ^3} + {\beta ^3} = 7$ so using ${a^3} + {b^3} = \left( {a + b} \right)\left( {{a^2} + {b^2} - ab} \right)$
We can say that ${\alpha ^3} + {\beta ^3} = \left( {\alpha + \beta } \right)\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right)$
Putting values from above we get
$7 = 3\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right)$
$\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right) = \dfrac{7}{3}$
Now $\left( {{\alpha ^2} + {\beta ^2} - \alpha \beta } \right)$
Since we know that ${a^2} + {b^2} + 2ab = {\left( {a + b} \right)^2}$
So, we can rewrite the above equation as ${\left( {\alpha + \beta } \right)^2} - 3\alpha \beta $
${\left( {\alpha + \beta } \right)^2} - 3\alpha \beta = \dfrac{7}{3}$
Again, substituting the values, we get
$9 - \dfrac{7}{3} = 3\alpha \beta $
Hence $\alpha \beta = \dfrac{{20}}{9}$
Now if sum of roots and product of roots is given that the quadratic equation can be written as ${x^2} - (sum{\text{ of roots)x + product = 0}}$
Thus, the quadratic equation having roots $\alpha $ and $\beta $ is ${x^2} - (\alpha + \beta )x + \alpha \beta = 0$
So, putting values we get
${x^2} - 3x + \dfrac{{20}}{9} = 0$
Therefore, on solving we get
$9{x^2} - 27x + 20 = 0$ which is the desired equation.
Note: Whenever we face such problems the key concept that needs to be in our mind is if somehow, we get the sum and the product of the roots then we can easily get the required quadratic equation. Hence simply accordingly to obtain sum and product of roots.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE